THE USE OF SHOW NOT TELL TECHNIQUE TO IMPROVE THE XI GRADE OF VOCATIONAL HIGH SCHOOL STUDENTS’ ABILITY IN WRITING SHORT STORY - Lilis Sadiah; Neneng Kartika; Enung Nurhayati (JLER (Journal of Language Education Research), 2019)
This study aims to determine the effectiveness of the show not tell technique on learning to write short stories in class XI Vocational School. The method used is one-group pretest-posttest design, which compares the experimental group before being given treatment (pretest) and after being treated (posttest). The research subjects were 33 Chemistry A class XI in Padalarang Vocational High School 4 as many as 33 people. The ability to write short stories is measured by writing tests composing short stories. The average value of pretest = 63.9, posttest average value = 73.7. There is an increase in the average value after treatment of: 73.7 - 63.9 = 9.8. The results of the pretest and posttest were then processed with SPSS, namely the normality test, variance homogeneity, and t test. The normality test obtained the P-Value (sig.) Value of the pretest value of 0.068, the posttest value of 0.072. P-Value (sig.) 5 0.05, meaning that both data are normally distributed. Test for homogeneity of P-Value (sig.) 0.661. Because P-Value (sig.) Is greater than 0.05, Ho is accepted, meaning that the variants of the two groups of values compared are homogeneous. The t-test of the sample is correlated, the value of Sig is obtained. (2 tailed) of 0,000. because t count  t table = 59.822  2.036 then Ho is rejected and Ha is accepted, meaning that there is an increase between the learning outcomes of writing short stories before and after using the show not tell technique.